Validation of deterministic code DRAGON5 for the fuel depletion analysis of a PWR pin-cell benchmark. (September 2021) - Al Zain, Jamal; El Hajjaji, O.; El Bardouni, T.; Lahdour, M.
Abstract: The purpose of this paper is to investigate the DRAGON5 accuracy for studying a PWR pin-cell benchmark, using the ENDF/B-VIII.0 nuclear data library based on 172 energy groups, in DRAGLIB format. This paper focuses on the neutronic and burn-up analysis of the Uranium fuel using DRAGON5 transport code. The precision of the deterministic Code DRAGON5 was validated by comparing Results obtained from analysis of the UO2 pin cell high burn-up benchmark with previously published literature values. The results of a study showed good agreement. Maximum absolute difference in infinite multiplication factor between DRAGON5 and CASMO-4 is found to be 0.23% for UO2 pin cell benchmark. Furthermore, the isotopic inventories and activities have been calculated/evaluated versus the fuel burn-up (BU) time for the natural UO2 fuel, and the enriched UO2 fuel at 1.2%. Highlights: The infinite multiplication factor during depletion is almost a linear function of fuel burnup. Study effect of burn up on neutron flux level. The inventory of isotopes calculated was consistent with similar studies. Good agreement was found between the present calculations and the previous published Results.